Excellence - Charalambous, Andreas (My University, 2026)
The application of nurses and patient’s satisfaction as indicators of quality of care in oncology units) was evaluated as “excellent” and the best among others and selected for funding by the Cyprus Research Promotion Foundation (26000€) for the programme “PENEK” (for young researchers).
Keywords: Sciences